GREEN JOBS AND THE POTENTIAL TO DIVERSIFY THE ENVIRONMENTAL WORKFORCE (Utah Environmental Law Review, 2011)
Normal 0 false false false EN-US X-NONE X-NONE /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Cambria","serif"; mso-ascii-font-family:Cambria; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Cambria; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} At the apogee of the 2008 election cycle not a day passed without mention of green jobs or green collar workers. In fact, one of the most enduring slogans of the campaign was "Jobs, baby, jobs." What was intriguing about this slogan was that it was a call for green jobs, but the term green collar is not new. As early as 1976, Professor Patrick Heffernan made reference to the coming "green collar revolution" in a congressional report. Despite the ubiquity of the term, there still is not consensus on what the term means or what constitutes a green job. The Department of Labor is trying to remedy this-it has placed a preliminary list of occupations that will be considered green jobs in the Federal Register and will begin collecting data on these. For the purposes of this discussion, I will use the term green jobs to encompass the range of jobs that are environmental in nature and that serve the purpose of environmental protection and sustainability. However, it is important to make further distinctions between different types of green jobs. Thus far, most studies of the environmental workforce have been concerned with the white collar sector of the green labor force. These are professional jobs typically requiring a bachelor's or graduate degree. However, some of the green jobs being promoted by politicians, think tanks, and grassroots activists alike are jobs social scientists traditionally described as blue collar jobs. These are skilled, semi-skilled, and unskilled jobs in manufacturing, installation, maintenance, the provision of services, and the like. The difference between these and traditional blue collar jobs is that the green collar jobs are being generated by companies using green technologies focused on sustainability, use of renewable resources, and have as their goal a reduction in the harmful effects of climate change. As Lucy Blake, CEO of the Apollo Alliance describes it, "A green-collar job is in essence a blue-collar job that has been upgraded to address the environmental challenges of our country."